Effect of cutting parameters on surface roughness in dry drilling of AISI D2 tool steel by using Taguchi Method - M.H. Osman1, M.H. Osman1; N.F. Tamin, N.F. Tamin; M.N. Ahmad1, M.N. Ahmad1; M.N. Ahmad1, M.N. Ahmad1; M.K. Wahid, M.K. Wahid; N.A. Maidin, N.A. Maidin; , M.H. Abu Bakar, , M.H. Abu Bakar; A.A. Azahar2, A.A. Azahar2 (UNIVERSITI TEKNIKAL MELAKA, 2018)
Hard drilling of AISI D2 reportedly produce accelerated wear to the cutting tool that detrimental to the surface finish. This paper presents the effect of drilling tool and drilling parameters by using Taguchi method to produce minimum surface roughness under dry conditions. The experiments were conducted using high speed steel (HSS) based drilling tools, coated with various coating layer (uncoated, TiN and TiCN) on material AISI D2 tool steel. Two cutting parameters, spindle speed and feed rate, each at three levels were considered. An L9 array, the signal-to-noise (S/N) ratio and the analysis of variance (ANOVA) were employed to analyze the significant and percentage of each parameters for minimum surface roughness. The results revealed that the drilling tools gave main affects the surface roughness based on the highest percentage distribution (95%), followed by the spindle speed (3%) and feed rate (0.4%). Further, the results of ANOVA indicated that the combination of optimum parameter recorded as drilling tools HSS-TiCN with spindle speed of 680 rpm and feed rate of 206.25 mm/min.